Peritoneal Carcinomatosis from Colon Cancer: A Systematic Review of the Data for Cytoreduction and Intraperitoneal Chemotherapy - Nadler, Ashlie; McCart, J. Andrea; Govindarajan, Anand (Clinics in Colon and Rectal Surgery, 2015)
A systematic review of the literature on the management of peritoneal carcinomatosis (PC) from colon cancer with cytoreductive surgery (CRS) and intraperitoneal chemotherapy (IPC) was undertaken using OVID Medline. Forty-six relevant studies were reviewed. Mean weighted overall morbidity following CRS and IPC was 49% (range 22–76%) and mortality was 3.6% (range 0–19%). Median overall survival ranged from 15 to 63 months, and 5-year overall survival ranged from 7 to 100%. This represents an improvement over historical treatment with systemic chemotherapy alone, even in the era of modern chemotherapeutic agents. Quality of life following surgery is initially decreased but improves with time and approaches baseline. Available data appear to support the treatment of PC from colon cancer with CRS and IPC. There is a large amount of variability among studies and few high-quality studies exist. Further studies are needed to standardize techniques.
Keywords: colorectal cancer; carcinomatosis; intraperitoneal chemotherapy; outcomes